Mediterranean diet in pregnancy is protective for wheeze and atopy in childhood. Issue 6 (15th January 2008) - Chatzi, L; Torrent, M; Romieu, I; Garcia-Esteban, R; Ferrer, C; Vioque, J; Kogevinas, M; Sunyer, J
Abstract : Introduction: Dietary intake of specific nutrients or food groups during pregnancy could play a role in the risk of asthma and atopy in offspring, but specific dietary patterns have not been implicated. The authors evaluated the impact of maternal (during pregnancy) and child adherence to a Mediterranean diet on asthma and atopy in childhood. Methods: Women presenting for antenatal care at all general practices in Menorca, a Mediterranean island in Spain, over a 12 month period starting in mid-1997 were recruited. 460 children were included in the analysis after 6.5 years of follow-up. Maternal dietary intake during pregnancy and children's dietary intake at age 6.5 years were assessed by food frequency questionnaires, and adherence to a Mediterranean diet was evaluated by a priori defined scores. During follow-up, parents completed questionnaires on the child's respiratory and allergic symptoms. Children underwent skin prick tests with six common aeroallergens. Results: The prevalence rates of persistent wheeze, atopic wheeze and atopy at age 6.5 years were 13.2%, 5.8% and 17.0%, respectively. One-third (36.1%) of mothers had a low quality Mediterranean diet during pregnancy according to the Mediterranean Diet Score, while the rest had a high score. A high Mediterranean Diet Score during pregnancy (at two levels, using "low" score as the reference) was found to be protective for persistent wheeze (OR 0.22; 95% CI 0.08 to 0.58), atopic wheeze (OR 0.30; 95% CI 0.10 to 0.90) and atopy (OR 0.55; 95% CI 0.31 to 0.97) at age 6.5 years after adjusting for potential confounders. Childhood adherence to a Mediterranean diet was negatively associated with persistent wheeze and atopy although the associations did not reach statistical significance. Conclusion: These results support a protective effect of a high level of adherence to a Mediterranean diet during pregnancy against asthma-like symptoms and atopy in childhood.